Green Synthesis of Iron Oxide Nanoparticles Using Hibiscus rosa sinensis Flowers and Their Antibacterial Activity - F. Buarki; H. AbuHassan; F. Al Hannan; F. Z. Henari (Journal of Nanotechnology)
Iron oxide nanoparticles (α- Fe2O3) were synthesized using an unconventional, eco-friendly technique utilizing a Hibiscus rosa sinensis flower (common name, China rose) extract as a reducer and stabilizer agent. The microwave method was successfully used for the synthesis of iron oxide nanoparticles. Various volume ratios of iron chloride tetrahydrate to the extract were taken and heated by the microwave oven for different periods to optimize iron oxide nanoparticle production. The synthesized iron oxide nanoparticles were characterized using the ultraviolet-visible spectrometer (UV-Vis), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and X-ray diffraction (XRD). X-ray diffraction confirmed the formation of α- Fe2O3 nanoparticles (hematite). The average size of iron oxide nanoparticles was found to be 51 nm. The antibacterial activity of the synthesized iron nanoparticles was investigated against different bacteria such as Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonia, and Escherichia coli. The results showed that the synthesized iron nanoparticles exhibited an inhabitation effect on all studied bacteria.